2020
DOI: 10.1101/2020.02.17.949990
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Granulocyte-Colony Stimulating Factor reduces cocaine-seeking and downregulates glutamatergic synaptic proteins in medial prefrontal cortex

Abstract: Background: Psychostimulant use disorder is a major public health issue, and despite the scope of the problem there are currently no FDA approved treatments. There would be tremendous utility in development of a treatment that could help patients both achieve and maintain abstinence. Previous work from our group has identified granulocyte-colony stimulating factor (G-CSF) as a neuroactive cytokine that alters behavioral response to cocaine, increases synaptic dopamine release, and enhances cognitive flexibilit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Thus, G-CSF signaling seems to be a potent regulator of dopamine neurons that allows for regulation of dopamine release and behavioral effects, without direct agonist/antagonist effects on dopamine release in the absence of other stimuli. Importantly, we also have demonstrated that treatment with G-CSF during abstinence after cocaine self-administration can reduce subsequent drug seeking behavior 10 .…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…Thus, G-CSF signaling seems to be a potent regulator of dopamine neurons that allows for regulation of dopamine release and behavioral effects, without direct agonist/antagonist effects on dopamine release in the absence of other stimuli. Importantly, we also have demonstrated that treatment with G-CSF during abstinence after cocaine self-administration can reduce subsequent drug seeking behavior 10 .…”
Section: Discussionmentioning
confidence: 69%
“…Dopamine release from terminals in the striatum is regulated by a wide range of neurotransmitter systems including acetylcholine, glutamate, GABA, various peptide systems and other types of signaling molecules (for review see Nolan et al, 2020 47 ). While we hypothesize that these effects do indeed occur through direct terminal regulation, glutamatergic neurons in the mPFC that project to the NAc are also known to play a role in the effects of G-CSF 6,10 . Thus, it is also possible that G-CSF is acting on cortical terminals in the NAc which alters NAc activity and dopamine release through a microcircuit.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations